Impact of climate change on oil palm production in Malaysia - Wan Mohd Noor, Wan Noranida (2022)
Climate change has significantly impacted the economic development and trade of developing countries, particularly those that largely rely on agriculture. Oil palm was the main contributor to the Gross Domestic Product (GDP) of the agriculture sector in Malaysia. Climate change affects the growth and production of oil palm in several ways, including reduction of sex ratio, disruption of the pollination process, abortion of newly formed inflorescences and spread of pests and diseases. Some quantitative research findings, including the Production Function approach, have produced inconsistent results, prompting this study to be conducted by introducing a supply response approach that has not been widely used in the country, particularly in estimating the impact of climate change on commodity crops. Hence, the goal of the study is to quantify the impact of climate change on oil palm production. Specifically, the study was designed to determine the best model for measuring the impact of climate change on oil palm production by using Supply Response and Production Function approaches, to estimate the short-run and long-run impact of the variables associated with climate variables and to predict the future impact of climate change on Malaysian oil palm production. Annual time series data (1980–2019) were collected and analyzed using appropriate time series econometric models: Autoregressive Distributed Lag (ARDL) and Error Correction Model (ECM). Estimated coefficients were constructed in linear and non-linear equations, in logarithmic form and subjected to and passed relevant diagnostic tests. Three simulation scenarios consisting of SN1 (minimum climate variability), SN2 (maximum climate variability) and SN3 (average climate variability) were employed to project the FFB production. The estimated shortrun coefficients of Model 3 show price factors respond significantly to increase oil palm production in the second lag period, and the expansion of the oil palm area has a positive relationship with oil palm production in the long-run consideration. The estimated coefficient of rainfall and temperature produces an adverse negative impact on oil palm production in the short run, while rainfall is an important variable for increasing oil palm production in the long run. The estimated short-term coefficients of Model 8 explain that own price and fertilizer use have a positive effect on oil palm production in the second lag period, and the increase in oil palm area is beneficial for oil palm production in the long run. The rainfall variable has a negative effect in the second lag period, but positively increases oil palm production in the long run. The results of forecasting analysis revealed that SN1, SN2, and SN3 would cause an increase in FFB production by 5%, 1% and 2%, respectively. The production of FFB under SN1 is expected to increase from 90.5 million Mt in 2021 to 122.2 million Mt in 2030, from 87.8 million Mt in 2021 to 9.10 million Mt in 2030 under SN2 and 89.2 million Mt to 105.6 million Mt over the same time period under SN3. The FFB yield under SN1 is predicted to increase from 16.75 tonnes/hectare in 2021 to 16.90 tonnes/hectare in 2030, a decrease in the FFB yield from16.71 tonnes/hectare to 16.57tonnes/hectare under SN2 and anticipated to decrease in FFB yield from 16.71 tonnes/hectare to 16.57 tonnes/hectare under SN3 within the same period. Overall, climate change is likely to reduce FFB yield in the future. These results would serve as empirical guides in helping policymakers, smallholders and agencies involved in oil palm production to make decisions in terms of practical and policy implications to adapt to climate change-related risks and uncertainties. Among the practical implications are investments in technologies, such as developing drought-tolerant and early-maturity crop varieties, controlling emerging pests and diseases, increasing water saving, and reducing evapotranspiration. Production and income insurance policies and disaster assistance could be one way to recover losses, especially for smallholders. In addition, law enforcement for all smallholders to comply with Malaysian Sustainable Palm Oil (MSPO) certificate requirements in operating oil palm plantations is necessary, apart from the introduction of policies such as the National Climate Policy (2009). The findings of this study will prompt a number of studies that require further investigation, such as the application of supply response on other crops and agricultural-related activities, considering other climate indicators such as radiation, light duration, CO₂ concentration, humidity and sea level, and divided regions such as Peninsular Malaysia, Sabah, and Sarawak in order to produce more accurate results regarding climate change scenarios.